2017
DOI: 10.3389/fnagi.2017.00061
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Genetic Screen Identifies Modifiers of Age-Dependent Amyloid β Toxicity in the Drosophila Brain

Abstract: The accumulation of amyloid β peptide (Aβ) in the brain of Alzheimer’s disease (AD) patients begins many years before clinical onset. Such process has been proposed to be pathogenic through the toxicity of Aβ soluble oligomers leading to synaptic dysfunction, phospho-tau aggregation and neuronal loss. Yet, a massive accumulation of Aβ can be found in approximately 30% of aged individuals with preserved cognitive function. Therefore, within the frame of the “amyloid hypothesis”, compensatory mechanisms and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Unlike budding and fission yeast, most human and fruit fly GI datasets were generated using either enhancement or suppression of an overexpressed hyperactive or dominant negative target gene ( Grimm, 2004 ; Jorgensen and Mango, 2002 ; St Johnston, 2002 ). This is typically followed by introduction of gene manipulation strategies that include RNAi, haploinsufficiency (removal of one copy of a gene in a diploid genome) or systematic overexpression of target genes ( Belfiori-Carrasco et al , 2017 ; Boutros and Ahringer, 2008 ; Gregory et al , 2007 ; Raymond et al , 2004 ; Therrien et al , 2000 ). These different manipulations can potentially convert what is classified as a negative GI in certain experimental contexts into a suppressor GI in other contexts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike budding and fission yeast, most human and fruit fly GI datasets were generated using either enhancement or suppression of an overexpressed hyperactive or dominant negative target gene ( Grimm, 2004 ; Jorgensen and Mango, 2002 ; St Johnston, 2002 ). This is typically followed by introduction of gene manipulation strategies that include RNAi, haploinsufficiency (removal of one copy of a gene in a diploid genome) or systematic overexpression of target genes ( Belfiori-Carrasco et al , 2017 ; Boutros and Ahringer, 2008 ; Gregory et al , 2007 ; Raymond et al , 2004 ; Therrien et al , 2000 ). These different manipulations can potentially convert what is classified as a negative GI in certain experimental contexts into a suppressor GI in other contexts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7). Likewise, PRCC encodes proline-rich protein PRCC‒PPIL2 complex, which acts as protein folding, transport and degradation in the brain of Alzheimer’s disease patients in previous study [33]. Other studies have also shown that PPIL2 interacts with intronic-miRNAs such as miR-130b in host genomes [34, 35].…”
Section: Discussionmentioning
confidence: 97%
“…The ease of access to large libraries of stocks has enabled numerous large-scale enhancer and suppressor screens. This type of screen has been extensively used in neurodegenerative disease models to help identify downstream pathways of toxicity ( Bilen and Bonini, 2007 ; Butzlaff et al, 2015 ; Zhang et al, 2015 ; Belfiori-Carrasco et al, 2017 ). The aim of these screens has been to identify factors that worsen (enhance) or ameliorate (suppress) the phenotype associated with a particular disease model.…”
Section: Drosophila As a Model Systemmentioning
confidence: 99%